Analysis of the effect of taxpayers and per capita income and private investment on local original income (PAD) and economic growth in Samarinda city - Ririn Dharmiyanti; Priyagus Priyagus; Rahcmad Budi Soeharto (Faculty of Economics and Business Mulawarman University, 2023)
The purpose of this study is to analyze and determine the effect of taxpayer influence analysis and per capita income as well as private investment on local original income (PAD) and economic growth in Samarinda City. The variables used in this study consist of exogenous variables (X), namely taxpayers, and per capita income and private investment, and endogenous variables (Y), namely Regional Original Income and Economic Growth. In this study, the type of data used was secondary data from 2006 – 2016. The analysis tool used is SPSS (statitical package for service solution) software version 23. From the results of the analysis, it is obtained that Taxpayers have a positive and significant effect on Regional Original Revenue. Per Capita Income has a positive and insignificant effect on Regional Original Income. Private Investment has a positive and insignificant effect on Local Original Income. Taxpayers have a positive and insignificant effect on Economic Growth. Per Capita Income has a positive and insignificant effect on Economic Growth. Private investment has a negative and insignificant effect on economic growth. Local Original Income has a negative and insignificant effect on Economic Growth. Regional Taxpayers have an indirect effect on Economic Growth through Local Original Revenue. Per Capita Income has an indirect effect on Economic Growth through Regional Original Income. Private Investment has an indirect effect on Economic Growth through Local Original Income.